Education about Ergonomics in the Workplace to Overcome Neck Pain in Computer Users - Irmayani, Irmayani; Ginting, Rosita; Bangun, Sri Melda; Samura, Jul Asdar Putra; Parinduri, Anggi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2023)
In an era where information technology has become an integral part of everyday life, the use of computers in the workplace has become the norm. Employees spend hours in front of computer screens to complete their tasks. However, a less recognized impact of prolonged exposure to computer devices is health problems, especially neck, shoulder and back pain. Ergonomics issues in computer use have become a major concern in today's work environment. This PKM activity aims to increase awareness of ergonomics in the workplace and overcome neck pain in workers who use computers regularly. Involving 45 participants, this activity focused on providing education that prioritizes ergonomic principles. Through presentations, discussions and live demonstrations, participants are provided with an in-depth understanding of the importance of correct work posture and the practical implementation of ergonomics principles in daily work routines. Initial assessment results showed that the majority of participants had unergonomic working postures. However, after participating in this activity, there was a significant increase in their understanding of ergonomics and awareness of the importance of correct posture in the workplace. The ergonomic solutions presented, such as chair arrangement, monitor position, and use of ergonomic accessories, were welcomed by participants as real steps in reducing neck pain. This article emphasizes the importance of awareness and practical application of ergonomics in the workplace to improve work health and comfort. It is hoped that this service can make a real contribution in reducing health problems such as neck pain in workers who use computers intensively, as well as improving the quality of their work